Co-firing of coal and woody biomass under conditions of reburning technology with natural gas - Nihad Hodžić; Kenan Kadic (International Journal of Renewable Energy Development, 2023)
It is a continuous imperative to establish the most efficient process of conversion of primary energy from fuel through combustion, which also has the least possible harmful effect on the environment. In this time of expressed demands for decarbonisation, it also means the affirmation of the use of renewable fuels and the indispensable application of appropriate primary measures in the combustion furnace. At the same time, the efficiency of the combustion process depends on several factors, from the type and properties of the fuel to the ambient and technological settings for the process. In this regard, with the aim of determining the static characteristics of combustion, experimental laboratory research was carried out on the combustion of mixtures of brown coal with low heating value and a high ash content with waste woody biomass and different process conditions: temperature, staged combustion air supply (air staging) and in conditions of application of a third or additional fuel (natural gas, reburning technology). Applied experimental methods included the analysis of the combustion process on the basis of input (reactants) - output (products), including the analysis of the composition of flue gases, i.e. the determination of the emission of the key components of flue gases CO2, CO, NOx and SO2, as well as the analysis of the composition of slag, ash and deposits ash, i.e. assessment and evaluation of the behaviour of ash from fuel in that process. Based on the obtained research results, this paper shows the significant positive effects of the application of primary measures in the furnace - compared to conventional combustion: air staging - reduction of net CO2 emissions during co-firing with biomass and reduction of NOx emissions by up to 30%; reburning technology - additional reduction of CO2 and NOx emissions in proportion to the share of natural gas, e.g. at a combustion process temperature of 1350 °C and at a 10% energy share of natural gas during the co-firing of a mixture of brown coal and waste woody biomass, compared to the emission without the use of natural gas, a reduction of NOx emissions by 185 mg/mn3 or by almost 30% was recorded. It was concluded, at the same time, the application of these primary measures in the furnace does not negatively affect the behaviour of ash from the fuel in the given settings of the combustion process.